2021
DOI: 10.1038/s41598-021-95230-0
|View full text |Cite
|
Sign up to set email alerts
|

OCTA reveals remodeling of the peripheral capillary free zones in normal aging

Abstract: The retinal neurovascular unit consists of blood vessel endothelial cells, pericytes, neurons, astrocytes, and Müller cells that form the inner retinal blood barrier. A peripheral capillary free zone (pCFZ) represents the distance that oxygen and nutrients must diffuse to reach the neural retina, and serves as a metric of retinal tissue oxygenation. The pCFZs are formed based on oxygen saturation in the retinal arterioles and venules. Because retinal arterioles contain a larger concentration of oxygenated bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…We obtained 20 × 20°OCTA images consisting of 512 b-scans, 512 A-scans per b-scan, 12 µm spacing between the b-scans, and 5 frames averaged per each b-scan location of the central fovea and of paired major arterioles and venules with their surrounding capillaries inferior to the fovea (Spectralis HRA + OCT; Eye Explorer version 1.10.4.0; Heidelberg Engineering, Germany; Fig. 1 ) as done previously [ 22 , 23 ]. The signal quality values (range for Spectralis = 0–40) of all our OCTA images from the vendor software were at least 20 to ensure good image quality.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We obtained 20 × 20°OCTA images consisting of 512 b-scans, 512 A-scans per b-scan, 12 µm spacing between the b-scans, and 5 frames averaged per each b-scan location of the central fovea and of paired major arterioles and venules with their surrounding capillaries inferior to the fovea (Spectralis HRA + OCT; Eye Explorer version 1.10.4.0; Heidelberg Engineering, Germany; Fig. 1 ) as done previously [ 22 , 23 ]. The signal quality values (range for Spectralis = 0–40) of all our OCTA images from the vendor software were at least 20 to ensure good image quality.…”
Section: Methodsmentioning
confidence: 99%
“…One issue with using the FAZ area as a biomarker for AD is that it is limited to a few or a single layer of capillaries. Moreover, it may become saturated with increasing disease severity and not increase further in size, even with the loss of capillaries [ 22 , 23 ]. FAZ area is highly variable in cognitively unimpaired (CU) older adults [ 23 , 25 28 ], and studies have shown that the FAZ area is not consistently significantly larger in an AD cohort than a control cohort [ 29 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations